Transformations : Immigration, family life, and achievement motivation among Latino adolescents - Suarez-Orozco, Carola 1957-; Suarez-Orozco, Marcelo M. 1956- (Stanford, Calif. : Stanford University Press, 1995)
"Explores migration between the US and Mexico and focuses on the differences among adolescent groups. The authors analyze four populations (native Mexican, native North Americans, first generation Latino immigrants, and second generation immigrants) and begin to unravel the difficult issues of cultural differences, social identity, family structure, and personal reasons for migrating" - Handbook of Latin American Studies, Vol. 57.
Includes bibliogr. references (p. 237-258) and index.
Keywords: Mexican American teenagers -- California; Mexican American teenagers; Achievement motivation in youth -- California; Teenagers -- Mexico; Achievement motivation in youth -- Mexico; Teenage immigrants -- California; Teenage immigrants -- United States; Mexico -- Emigration and immigration